PENGABDIAN MASYARAKAT: PELATIHAN PENGGUNAAN MICROSOFT EXCEL PADA SISWA/I SD GMIT BELEMANA - Sali, Yulia Mau; Mauko, Marcella; Hinglir, Yakoba; Bagaisar, Yosua; Abollanuha, Yeni; Letsama, Yusuf; Mauleti, Susana; Molina, Jon Idrison (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Computer technology is a crucial aspect of daily life; however, many individuals, including students of SD GMIT Belemana, struggle to operate computers effectively. To address this issue, we conducted a Microsoft Excel training program aimed at enhancing students' abilities to adapt to technology. The training involved both theoretical explanations and hands-on practice. The activities included inputting data into columns, organizing tables neatly, and learning how to save their completed files. This training is expected to improve students' skills in utilizing technology, particularly Microsoft Excel, in the educational field, ultimately fostering a generation that can adapt to technological advancements and apply Microsoft Excel effectively. The method employed was a direct training approach, where we also introduced students to the various symbols used in Microsoft Excel. The results of this training showed that students experienced significant improvement in their ability to operate Microsoft Excel correctly and effectively, enabling them to apply the program in practical scenarios.